THE HIDDEN COSTS OF WORKAHOLISM - TRAȘCĂ OTILIA MARIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This paper examines the hidden costs associated with workaholism, a behavioral phenomenon characterized by an uncontrollable drive to work excessively, often beyond what is required or expected. While workaholism is frequently celebrated in corporate cultures that equate long hours with commitment and success, recent research underscores its adverse effects on mental health, physical well-being, and overall life satisfaction. Through an analysis of contemporary studies, this paper presents the distinctions between healthy work engagement and workaholism, noting that while one is associated with motivation and well-being, the other one aligns more closely with behavioral addiction and compulsive tendencies. Workaholism has been shown to foster a toxic interplay between the constant urge to remain connected to work and diminished self-compassion, resulting in increased levels of burnout, heightened stress, and limited recovery opportunities. Moreover, excessive work hours have been linked to serious physical health consequences, including sleep deprivation, poor dietary habits, and elevated risk of cardiovascular diseases, particularly in high-income OECD countries. Socially, workaholism exacerbates isolation by cutting time available for family and social interactions, thus weakening essential support networks. This paper emphasizes that the glorification of workaholism detracts from sustainable productivity and undermines both professional and personal fulfillment. By adopting a holistic approach to professional success that prioritizes mental health, physical well-being, and personal relationships, individuals and organizations alike can work toward achieving meaningful, long-term fulfillment and resilience in an increasingly demanding professional landscape.